A Framework for Comprehensive Dairy Calf Health Investigations - Kristen Y. Edwards; David L. Renaud (Animals)
The objective of this narrative review is to provide a systematic framework for veterinarians to investigate dairy calf health, focusing on critical control points and key performance indicators (KPIs) to address morbidity and mortality challenges in preweaned calves. Recommendations target prenatal maternal nutrition, heat stress abatement, and optimal calving management to minimize risks associated with perinatal mortality and preweaning morbidity. Further, comprehensive colostrum management is discussed to ensure excellent transfer of passive immunity, which includes prompt collection and feeding within two hours of birth at a volume of 8.5–10% of calf body weight. Nutritional guidance emphasizes the importance of transition milk and feeding higher planes of nutrition to support immunity, with recommendations that milk total solids exceed 10% to meet energy needs. Environmental management recommendations include a minimum of 3.3 m2 of space per calf, the use of low-dust bedding, and air quality controls to reduce respiratory disease. Lastly, regular health data collection and KPI monitoring, such as average daily gain and morbidity rates, are essential for data-driven improvements. By implementing these evidence-based recommendations, veterinarians can support dairy farmers in reducing calf morbidity and mortality, ultimately enhancing calf welfare and lifetime productivity.